PENGARUH ANGKA TUBERKULOSIS TERHADAP ANGKA KEMISKINAN DI INDONESIA : STUDI KASUS 407 KABUPATEN KOTA - Sihaloho, Estro Dariatno; Kamilah, Fariza Zahra; Rahma, Gina Ridhia; Kusumawardani, Salsabila; Hardiawan, Donny; Siregar, Adiatma YM (Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study aims to determine the effect of the Tuberculosis rate on the poverty rate in 407 municipal districts in Indonesia in 2017. This study uses the Multiple linear regression (MLR) method with STATA 14. The results of the study indicate that the Tuberculosis rate has a positive effect - significant on the poverty rate, gdrp per capita has a negative effect – significant on poverty rate, and total health workers have a negative effect - significant on Tuberculosis cases. Keywords: poverty, gdrp per capita, health workers, tuberculosisJEL Classification:I32, O12, J83, I15